Hybride Formen urbaner Produktion durch Digitalisierung? Trends und Beispiele aus Nordrhein-Westfalen - Busch, Hans-Christian; Mühl, Caroline; Fuchs, Martina; Fromhold-Eisebith, Martina (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
Building on current debates on digitalisation and spatial development processes, this paper aims to explore to what extent digitally enhanced production technologies, such as Industry 4.0, enable the emergence of new forms of urban production. Based on theoretical and conceptual considerations, empirical insights are derived from 41 interviews conducted with experts in eight industrial cities in the German state of North Rhine-Westphalia. The results indicate that the commercial application of new digital production technologies instigates novel forms of hybrid digital urban manufacturing which change patterns of previous value creation. The paper develops a more precise understanding of these value creation processes and the locational embeddedness of hybrid digital urban manufacturing.
Keywords: Urban production; Digital transformation; Hybrid production; Problem-solving cycle; North Rhine-Westphalia